Incidental occurrence and risk factors of brucellosis in teaching hospital - Imad Ibrahim Ali Al-Sultan; Tarik I.Ali; O. E.Ibrahim (2011)
Brucellosis is an important public health problem in many developing countries. The disease represents a health problem in Yemen, therefore continued to be notified with increasing frequency in Thamar province. The main them of reviewing the importance of incidental rate of disease existence is to analyze the demographic features of brucellosis patients hospitalized in a teaching hospital at the period 2005-2007.Total patients under study were 212 at that period. Patients represent a high rate of incidental occurrence 16/1000 of total admission most of them were females 124 (58%) while male cases are 88 (41.5%). The patients from rural areas (68.4%) were of high susceptibility to disease than patients reside at urban regions (31.6%). High risk patients were identified in age group of (11-20) years then in (21-30) year’s old people and at patients of ten years old or less. The frequency of seasonal infection with brucellosis at spring season was more than any other seasons in the year. Analysis of the significance of risk factors of infection in relation to occupation and work of patients indicate that housewife’s with the higher rate of infection (13.7),followed by raw milk drinkers(11.8%), then farmers(8.5%), then Shepherds and health workers each the same rate of infection (7.1%). Butchers and meat handlers represent (6.6%) and was the lowest infection rate.